Local Wisdom Values as a Social Control Mechanism among Communities Surrounding Kali Cilik Temple, Blitar Regency, Indonesia - Desita Fitria Cahyani; Amanah Agustine (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2026)
The rapid development of technology has the potential to erode the value of wisdom in community life. On the other hand, studies on local wisdom around the Kali Cilik Temple site in Blitar are still limited. The research to analyze the relevance of local wisdom and examine community efforts to mantain these traditional values in the modern era. This research uses a qualitative research method with a descriptive approach. Data was collected through field obsevations and interviews with temple guards and local residents. The research result show tht the community around Candirejo village, Ponggok District, contains myths and social taboos that function effectively as instruments for controlling community behavior. In addition, the differences in religious beliefs held by the local ciommunity do nott prevent the community form participating in cultural spaces such as the Desa Traditional. The study makes a theoretical contribution by demonstrating that wisdom rooted in a historical site can transform into a guardian of ethics for the community surrounding Kalicilik Temple in tnne modern era.